Mapping materials, drawing Europe: Sample and data quality and accessibility in the biobanking infrastructure BBMRI-ERIC - Erik Aarden (Big Data & Society)
The European biobanking infrastructure BBMRI-ERIC was established in the context of European Union science policy to facilitate collaboration between European repositories of biological samples and associated data, or so-called biobanks. To allow the exchange of research materials, the infrastructure has created several platforms for quality management and making materials visible and accessible. In this article, I develop the metaphor of mapping to explore the workings of these platforms. I consider maps as devices for giving directions, as representations of science, and as (symbolic) outlines of the territory of Europe to explore how BBMRI-ERIC's activities in quality management and IT-platforms for making materials visible and accessible (aim to) facilitate circulation. Across the different platforms, efforts to harmonize and integrate European biobanking activities confront both scientific and European tendencies toward fragmentation. The map of a European biobanking community drawn by BBMRI-ERIC consequently both makes and unmakes Europe sketching a Europe of both harmonization and fragmentation. In laying bare these paradoxical effects of the construction of a European biobanking infrastructure, using mapping as a lens shows how, rather than realizing its much-cited role as a “facilitator” for research, BBMRI-ERIC embodies key tensions at the center of efforts to advance “data-based” (big) science.